The Impact of Nashirudin Al Albani's Tarjih Hadith Method on Differences in Mazhab and Qur'anic Interpretation - Saladin, Bustami; Taufiq, Muhammad; Ibni Syatirah, Sebti (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The Impact of Nashirudin Al-Albani's Tarjih Hadith Method on Differences in Mazhab and Qur'anic Interpretation